Case Report: Nontuberculous mycobacterial infections in children with complete DiGeorge anomaly - Hicks, Elizabeth Daly; Agada, Noah O.; Yates, Tyler R.; Kelly, Matthew S.; Tam, Jonathan S.; Ferdman, Ronald M.; Dibernardo, Louis R.; Madden, John F.; Moody, M. Anthony; Markert, Mary Louise (Frontiers in Immunology, 2023)
Children with complete DiGeorge anomaly (cDGA) have congenital athymia, resulting in severe T cell immunodeficiency and susceptibility to a broad range of infections. We report the clinical course, immunologic phenotypes, treatment, and outcomes of three cases of disseminated nontuberculous mycobacterial infections (NTM) in patients with cDGA who underwent cultured thymus tissue implantation (CTTI). Two patients were diagnosed with Mycobacterium avium complex (MAC) and one patient with Mycobacterium kansasii. All three patients required protracted therapy with multiple antimycobacterial agents. One patient, who was treated with steroids due to concern for immune reconstitution inflammatory syndrome (IRIS), died due to MAC infection. Two patients have completed therapy and are alive and well. T cell counts and cultured thymus tissue biopsies demonstrated good thymic function and thymopoiesis despite NTM infection. Based on our experience with these three patients, we recommend that providers strongly consider macrolide prophylaxis upon diagnosis of cDGA. We obtain mycobacterial blood cultures when cDGA patients have fevers without a localizing source. In cDGA patients with disseminated NTM, treatment should consist of at least two antimycobacterial medications and be provided in close consultation with an infectious diseases subspecialist. Therapy should be continued until T cell reconstitution is achieved.